The Potential of Indigenous Lactic Acid Bacteria Lactobacillus Plantarum Dad 13 in Ice Cream as Probiotic Food - B. R. D Wulandani; D. Kisworo; Bulkaini Bulkaini; W. Yulianto; Haryanto Haryanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Worldwide demand for functional food will continue to increase rapidly due to increasing public awareness about the impact of food on health. One example of functional food is milk-based food which contains probiotic bacteria such as yogurt, cheese, and ice cream. Among probiotic dairy products, ice cream is the ideal matrix delivery of probiotic ingredients to the human body. This study aimed to find the potential of L. plantarum dad 13 in ice cream as a probiotic food through the growth pattern of the resulting lactic acid bacteria and to obtain the best incubation time and aging time for the physicochemical properties of the ice cream produced. The experimental design in this study used a Randomized Block Design (RBD), which was arranged in a factorial manner with 2 factors. The first factor is the length of incubation time which consists of 3 levels, namely 0, 5, and 10 hours; and the second factor is the length of aging which consists of 3 levels, namely 24, 48, and 72 hours. The results showed that the viability of lactic acid bacteria in ice cream with the addition of lactic acid bacteria L. plantarum dad 13 was more influenced by the pH value during the aging process, and there was an interaction between the incubation time and the aging time on the viability of the lactic acid bacteria L. plantarum dad 13 in ice cream, as well as the antioxidant activities, produced.